The Effects of Lens Extraction Surgery on Intraocular Pressure and Anterior Segment Parameters in Primary Angle-Closure Glaucoma - Serdar Bayraktar; Büşra Dilara Yıldırım Erdal; Fatma Büşra Altaş; Mine Türkay; Emine Şen (Türk Oftalmoloji Dergisi)

(untitled)
Objectives:To investigate the effects of phacoemulsification with intraocular lens implantation (phaco+IOL) surgery on intraocular pressure (IOP) and anterior segment parameters in patients with cataract and primary angle-closure glaucoma (PACG).Materials and Methods:Fifty-five patients with PACG undergoing phaco+IOL surgery were evaluated in terms of best corrected visual acuity (BCVA), IOP, anterior chamber depth (ACD), aqueous depth (AD), and lens thickness (LT) measured by optical biometry preoperatively and at the 6-month postoperative visit. They were compared with 34 healthy age-and gender-matched cataract patients who underwent phaco+IOL surgery.Results:Preoperative evaluation revealed higher IOP, shorter axial length, shallower ACD and AD, and greater LT in the PACG group (p<0.001 for all). Postoperative evaluation in the PACG group showed an increase in BCVA, a significant decrease in IOP, an increase in ACD and AD, and a decrease in LT (p<0.001 for all). Additionally, a reduction in the average number of antiglaucomatous medications used postoperatively was observed in the PACG group (p<0.001). The changes in IOP, ACD, AD, and LT between preoperative and postoperative assessments were significantly greater in the PACG group compared to the control group (p<0.0001 for all).Conclusion:Phaco+IOL surgery in PACG patients leads to a significant increase in ACD compared to the control group and allows better control of IOP with fewer antiglaucomatous medications after surgery.